PEMBERDAYAAN UMKM BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI KABUPATEN KENDAL MENUJU PASAR GLOBAL - Supri Hadi; Agustinus Fritz Wijaya; Birmanti Setia Utami (Universitas Kristen Duta Wacana, 2016)
Free trade can not be dammed again, so the impact on local businesses in particular products SME have to be able to compete with foreign products because it is supported by information and communication technology (ICT), which consists of the online market. KKN-PPM FTI UKSW was carried out to community groups businesses incorporated in the SME Kabupaten Kendal, Central Java, was carried out with methods of mentoring and development applications online market. The purpose of this program is to provide ICT field for the empowerment of the perpetrators of the SME. KKN-PPM program results are the SME capable of using ICT in particular basic creative multimedia designer label to product packaging, design content market online, and can make your business, as well as brend is able to manage the online market site independently, so the product SME Kabupaten Kendal as a potential area capable of leading to the global market.